Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1007/s11661-010-0551-5
|View full text |Cite
|
Sign up to set email alerts
|

Austenite Formation in Plain Low-Carbon Steels

Abstract: In this study, austenite formation from hot-rolled (HR) and cold-rolled (CR) ferrite-pearlite structures in a plain low-carbon steel was investigated using dilation data and microstructural analysis. Different stages of microstructural evolution during heating of the HR and CR samples were investigated. These stages include austenite formation from pearlite colonies, ferrite-to-austenite transformation, and final carbide dissolution. In the CR samples, recrystallization of deformed ferrite and spheroidization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
46
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(66 citation statements)
references
References 23 publications
5
46
0
1
Order By: Relevance
“…The volume fraction of austenite was determined via analyzing the dilatometric data employing the lever rule, details of which can be found elsewhere. 21) All microstructures were analyzed in the transverse plane of the rolled sheet, i.e. the through thickness plane perpendicular to the rolling direction.…”
Section: Materials and Experimental Proceduresmentioning
confidence: 99%
“…The volume fraction of austenite was determined via analyzing the dilatometric data employing the lever rule, details of which can be found elsewhere. 21) All microstructures were analyzed in the transverse plane of the rolled sheet, i.e. the through thickness plane perpendicular to the rolling direction.…”
Section: Materials and Experimental Proceduresmentioning
confidence: 99%
“…Mohanty et al [16] reported that higher heating rate results in relatively larger volume fraction of austenite in the range of lower intercritical temperatures. Azizi-Alizamini et al [17] investigated the austenite formation of hot-rolled and cold-rolled ferrite-pearlite structures. They showed that a delay in spheroidization of cementite lamellae and recrystallization of ferrite grains in the cold-rolled steel with increasing heating rates from 1°C/s to 900°C/s.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that the transformation of austenite to pearlite during cooling was accelerated by the small size of the austenite grains. 12,23,24 URA with a heating rate of 600°C/s up to 730°C does not show a homogeneous grain refinement. This microstructure ( Figure 5) consists of two-sized grains of 10 μm and 2 μm.…”
Section: Resultsmentioning
confidence: 87%
“…URA shifts the start temperature of recrystallization to higher values near and above Ac 1 . 3,[7][8][9][10][11][12][13][14][15] So, in the intercritical temperature range, recrystallization and phase transformation proceed concurrently and with a mutual "interaction". The intensity of the interaction depends of the amount of stored energy and determines the final microstructure of the steel.…”
Section: Introductionmentioning
confidence: 99%